Histochemical and Functional Improvement of Adipose-Derived Stem Cell-Based Tissue-Engineered Cartilage by Hyperbaric Oxygen/Air Treatment in a Rabbit Articular Defect Model. (May 2015) - Dai, Niann-Tzyy; Fan, Gang-Yi; Liou, Nien-Hsien; Wang, Yi-Wen; Fu, Keng-Yen; Ma, Kuo-Hsing; Liu, Jiang-Chuan; Chang, Shun-Cheng; Huang, Kun-Lun; Dai, Lien-Guo; Chen, Shyi-Gen; Chen, Tim-Mo
Abstract : Abstract: Cartilage is exposed to compression forces during joint loading. Therefore, exogenous stimuli are frequently used in cartilage tissue engineering strategies to enhance chondrocyte differentiation and extracellular matrix (ECM) secretion. In this study, human adipose-derived stem cells were seeded on a gelatin/polycaprolactone scaffold to evaluate the histochemical and functional improvement of tissue-engineered cartilage after hyperbaric oxygen/air treatment in a rabbit articular defect model. Behavior tests showed beneficial effects on weight-bearing and rear leg-supporting capacities after treatment of tissue-engineered cartilage with 2.5 ATA oxygen or air. Moreover, positron emission tomography images and immunohistochemistry staining demonstrated hydroxyapatite formation and increased ECM synthesis, respectively, at the tissue-engineered cartilage graft site after high pressure oxygen/air treatment. Based on these results, we concluded that hyperbaric oxygen and air treatment can improve the quality of tissue-engineered cartilage in vivo by increasing the synthesis of ECM.